Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1021/acs.biochem.5b00190
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Thio Effects in the Hepatitis Delta Virus Ribozyme Reveal that the Reaction Pathway Is Controlled by Metal Ion Charge Density

Abstract: The hepatitis delta virus (HDV) ribozyme self-cleaves in the presence of a wide range of monovalent and divalent ions. Prior theoretical studies provided evidence that self-cleavage proceeds via a concerted or stepwise pathway, with the outcome dictated by the valency of the metal ion. In the present study, we measure stereospecific thio effects at the nonbridging oxygens of the scissile phosphate under a wide range of experimental conditions, including varying concentrations of diverse monovalent and divalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
78
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(87 citation statements)
references
References 66 publications
6
78
1
Order By: Relevance
“…However, unlike typical results for other metalloribozymes (Frederiksen and Piccirilli 2009), the metal rescue is unconventional in that the substitution decreases the susceptibility of the ribozyme to inhibition by thiophilic metal ions rather than being activated by their presence (Thaplyal et al 2013). Recent studies of stereospecific thio effects over a wide range of ionic conditions reveal inverse thio effects at the pro-S P position with large monovalent and divalent ions (Thaplyal et al 2015). These results, taken together with pH-rate profiles, proton inventories, ammonium/imidazole rescue experiments, and computational simulations, have been interpreted to suggest that the HDVr mechanism can shift from a concerted metal ion-stabilized to a stepwise proton transfer-stabilized pathway with decreasing metal ion charge density (Thaplyal et al 2015).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, unlike typical results for other metalloribozymes (Frederiksen and Piccirilli 2009), the metal rescue is unconventional in that the substitution decreases the susceptibility of the ribozyme to inhibition by thiophilic metal ions rather than being activated by their presence (Thaplyal et al 2013). Recent studies of stereospecific thio effects over a wide range of ionic conditions reveal inverse thio effects at the pro-S P position with large monovalent and divalent ions (Thaplyal et al 2015). These results, taken together with pH-rate profiles, proton inventories, ammonium/imidazole rescue experiments, and computational simulations, have been interpreted to suggest that the HDVr mechanism can shift from a concerted metal ion-stabilized to a stepwise proton transfer-stabilized pathway with decreasing metal ion charge density (Thaplyal et al 2015).…”
Section: Introductionmentioning
confidence: 91%
“…Detailed biochemical and kinetic studies have revealed multiple functional divalent metal binding sites and demonstrated that molar concentrations of monovalent ions alone can support catalysis (Nakano et al 2001(Nakano et al , 2003. Sitebound metal ion interactions have been identified and characterized via crystallography (Ke et al 2004(Ke et al , 2007Chen et al 2010), spectroscopy ), chemical probing experiments (Chen et al , 2013Lévesque et al 2012;Thaplyal et al 2015), and molecular simulation (Lee et al 2011;Veeraraghavan et al 2011a,b;Chen et al 2013). Moreover, pH-rate profiles for the reaction in the absence of Mg 2+ and for mutants designed to disrupt binding of the proposed active site ion are inverted relative to the reaction of the native HDVr in Mg 2+ Chen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Most known RNA-cleaving enzymes bind metal using the pro-Rp oxygen; when this oxygen is replaced by sulfur, the activity is significantly suppressed (typically by 30-200 fold). 32,[48][49][50][51] On the other hand, if the pro-Sp oxygen is replaced by sulfur, the enzyme remains quite active (with only a several fold drop in activity).…”
Section: Further Increase Of Ph Even Decreased the Rate Most Rna-clementioning
confidence: 99%
“…The PS modification has been used for probing ribozyme mechanisms, designing anti-sense oligonucleotides, and assembling nanomaterials. [35][36][37][38][39][40] Since Cu 2+ is a thiophilic soft metal, we herein use a PS containing library for selecting new DNAzymes in the presence of Cu 2+ , and develop a biosensor for Cu 2+ detection.…”
Section: Introductionmentioning
confidence: 99%